Combined use of (99m)technetium-labelled macroaggregates of albumin and (75)selenium-selenomethionine in the diagnosis of lung cancer - Critchley, Mair (1974)
Critchley, M., Testa, H. J., and Stretton, T. B. (1974).Thorax, 29, 421-424. Combined use of (99m)technetium-labelled macroaggregates of albumin and (75)selenium-selenomethionine in the diagnosis of lung cancer. A two-stage isotope technique has been used in 30 patients with radiographic evidence of circumscribed pulmonary lesions in an attempt to establish the nature of the underlying pathological process. The test was carried out as a `blind' procedure without knowledge of the findings of investigations other than the plain chest radiograph. An initial scan was performed with (99m)technetium-labelled macroaggregated albumin. The view showing the lesion most clearly was selected and a second scan was obtained after an intravenous injection of (75)Se-selenomethionine. Scans were interpreted by comparison of the `cold area' on the technetium scan with the corresponding area on the selenomethionine scan. Accumulation of (75)Se-selenomethionine at the site corresponding to the lesion is described as a positive result and absence of accumulation as negative. The findings suggest that there is selective uptake of (75)Se-selenomethionine by primary bronchogenic carcinoma; in the few patients with secondary carcinomas and non-malignant disease investigated so far, the lesion has failed to concentrate (75)Se-selenomethionine.